REVITALISASI NILAI-NILAI HADIS DALAM DAKWAH DIGITAL: Studi Integratif tentang Trauma Religius dan Podcast Islami - Yenanda Putri Zanuba (DIRAYAH : Jurnal Ilmu Hadis, 2025)
Religious trauma is a psychological problem that arises as a result of painful spiritual experiences, such as abuse of religious teachings or excessive pressure from religious aspects. In this situation, digital da’wah through podcast media can offer a more inclusive, in-depth, and calming alternative. This article aims to explores how the prophetic values ​​contained in the hadith can be revived through Islamic podcasts as a response to religious trauma. This study applies a qualitative approach with content analysis of several episodes of the Escape podcast hosted by Ustadz Felix Siauw and Raymond Chin. The findings of the study indicate that the values ​​in the hadith such as rahmat (compassion), hikmah (wisdom), and tazkiyatun nafs (purification of the soul) are expressed in a narrative form that is free from judgment, encourages introspection, and strengthens spiritual connections. Thus, Islamic podcasts have the potential to be a means of digital da’wah that is sensitive to situations of religious trauma, especially among the younger generation of Muslims.